Effect of induced interference and the formation of spatial perturbation fine structure in nonequlibrium open-ended system - Kuklin, V.M. (Вопросы атомной науки и техники, 2006)
It is shown, that the modes of unstable spectrum of instability near threshold are able to form long-living spatial
fine structure and anomalous interference splashes, induced by the pump. Показано, что моды нестабильного спектра неустойчивости вблизи порога способны сформировать долго живущую тонкую структуру и аномальные интерференционные всплески, индуцированные накачкой. Показано, що моди нестабільного спектру нестійкості поблизу порогу здібні сформувати тривало живучу
тонку структуру та аномальні інтерференційні сплески, індуковані накачкою.